Struktur Klausa dan Hubungan Sintaktis dalam Artikel Argumentatif di Website Badan Bahasa Edisi 2025 - Bagas Cahyadi; Cicha Kartikha Sri Mulyani; Era Nur'aini; Esa Futuh Handa; Rahma Delviani; Asep Purwo Yudi Utomo; Noviani Achmad Putri; Khanifa Kinanthi Aulina (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study examines clause structures and syntactic relations in argumentative articles published on the 2025 edition of the Badan Bahasa website. As a communication tool, language plays a crucial role in conveying ideas and shaping logical reasoning, particularly in argumentative texts that require a high degree of cohesion and coherence. The research aims to describe the patterns of clause structure and interclausal syntactic relations used in these articles to understand how linguistic constructions influence argumentative strength. Employing a qualitative descriptive approach with the distributional method, the study relies on internal linguistic elements as analytical instruments. The findings show that the articles generally employ single clauses with S–P–Pelengkap patterns as well as complex clauses expressing causation, alongside syntactic relations that include coordination and subordination, including causal, contrastive, purposive, and additive relations. These patterns indicate consistent application of Indonesian syntactic rules, although some repetitive tendencies appear in the use of active clauses and multi-layered complex sentence structures. The study highlights the importance of mastering clause structure in constructing logical, persuasive argumentative texts, and the findings are expected to serve as a reference for writers and language institutions to improve academic writing quality and enrich linguistic studies in digital contexts.